Efforts to Increase Motivation of KURABA (Toddler Home Visits) Cadres Using a Teleposyandu Approach at Posyandu Mawar, Bangkalan District - M. Suhron; Elis Agusriyanti; M. Hasinuddin; Eny Susanti (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Motivation for Home Visits by Posyandu cadres is an implementation of the Ministry of Health, but cadre motivation is still lacking in Home Visits by Posyandu cadres. Analyzing the Motivation of Kuraba Cadres (Five-Year-Old Baby Home Visits) Using the Teleposyandu Approach at Posyandu Mawar Bangkalan. Type of experimental research: pre-post test One Group Design, sampling technique with simple random sampling, a sample size of 20 cadres, analyzed statistically using the Wilcoxon test. There was an increase in cadre motivation for KURABA (Toddler Home Visits) between before and after the intervention was given Teleposyandu at Posyandu Mawar Bangkalan, apart from that, based on the Wilcoxon Test analysis on satisfaction, the P value was (0.000) < α (0.05).